Effect of Microwave-Assisted Enzymatic Aqueous Extraction on the Quality Attributes of Maize (Zea mays L.) Seed Oil - Anwar, Farooq; Yaqoub, Ammara; Ali Shahid, Shaukat; Manzoor, Maleeha (Asian Journal of Chemistry, 2013)
The present work evaluates and compares the quality characteristics of microwave-assisted enzymatic aqueous extracted maize (Zea mays L.) seed oil with those of hexane-extracted oil and control oil. The oil content from microwave-assisted enzymatic aqueous extracted maize seeds was found to be 2.52-3.60 % compared with 2.22-3.32 % in control seeds, revealing an increment of 10-11 % in the oil extraction yield due to microwave enzymatic treatment. The physicochemical parameters such as density, refractive index, free fatty acid, iodine value, colour, saponification number and unsaponifiable matter and fatty acids composition of the microwave-assisted enzymatic aqueous extracted maize oil were quite comparable with those of hexane-extracted oil and control oil, showing no significant (p > 0.05) differences among the extraction methods. The oxidative stability of the microwave-assisted enzymatic aqueous extracted oil was found to be considerably improved in comparison to the control oil and hexane- extracted oil as evident by the determinations of conjugated dienes, conjugated trienes, peroxide and p-anisidine values. It was concluded that microwave-enzymatic adjuvant improved the oil extraction yield as well as the oxidation properties of the oil produced without altering its other quality attributes.